2021
DOI: 10.1111/liv.14788
|View full text |Cite
|
Sign up to set email alerts
|

From NAFLD to MAFLD: Nurse and allied health perspective

Abstract: Fatty liver disease associated with metabolic dysfunction is the most prevalent liver disease worldwide, though both patient and health professional still lack awareness of it. An international consensus panel has produced what is sure to be an influential report renaming the disease from non‐alcoholic fatty liver disease (NAFLD) to metabolic (dysfunction) associated fatty liver disease (MAFLD) and suggesting how the disease should be diagnosed. This viewpoint explores the call from the perspective of nurse an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 86 publications
0
36
0
Order By: Relevance
“…Since the MAFLD consensus was proposed in early 2020, it has received a lot of support from experts, liver associations, nurses, and patient advocacy groups. [16][17][18][19] They all agreed to rename NAFLD to MAFLD. At present, the Association for the Study of the Liver in Latin America, Asia, Middle East, North Africa, and Sub-Saharan Africa have published clinical practice guidelines for MAFLD based on the characteristics of the local population.…”
Section: Introductionmentioning
confidence: 99%
“…Since the MAFLD consensus was proposed in early 2020, it has received a lot of support from experts, liver associations, nurses, and patient advocacy groups. [16][17][18][19] They all agreed to rename NAFLD to MAFLD. At present, the Association for the Study of the Liver in Latin America, Asia, Middle East, North Africa, and Sub-Saharan Africa have published clinical practice guidelines for MAFLD based on the characteristics of the local population.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100][101][102][103][104][105][106][107][108] However, others have suggested to retain the NAFLD name/acronym, and they argued that there is an ambiguity of the term "metabolic", and the change can lead to some confusion for stakeholders and may have potential impediment of drug development and regulatory approvals. 109 Recent study has showed that this is unlikely to be the case, as the change from NAFLD to MAFLD led to increased awareness of fatty liver disease in primary care physicians and specialists. 104 Thus, although there is evidence that MAFLD is highly prevalent, it is very likely that these data under-rather than over-estimate the actual magnitude of the disease because the previous diagnostic criteria of NAFLD are based on the exclusion of other liver diseases.…”
Section: The Switch From Nafld To Mafld: Impli C Ati On For S Vr Pamentioning
confidence: 99%
“…In Mexico, the lack of awareness of MAFLD by physicians has been associated with misdiagnosis and inappropriate treatment and has underestimated the serious consequences of this disease [ 12 ]. There has been a high level of acceptance of the new name among patients [ 13 ], primary care physicians [ 14 ], nurses, and allied health professionals [ 15 ]. This acceptance of the use of MAFLD as a medical term may be due to its clinical relevance and its value in clinical communication [ 15 ].…”
Section: Introductionmentioning
confidence: 99%